Experimental and Numerical Analysis of Normal and Lateral High-Velocity Impacts on Carbon Fiber-Reinforced Polymer Laminates - Huang, T.; Liu, Z.C.; Wang, Y.L. (Проблемы прочности, 2016)
This paper examines the effects of normal and lateral high-speed impacts on carbon fiber-reinforced polymer laminates. Experimental tests were conducted at varying velocities (120–200 m/s), and the differing damage modes between normal and lateral impacts were analyzed. Dynamic finite element analysis was performed to simulate the damage process using the finite element software ABAQUS. The simulation shows a good correlation with the experimental results.